RENAL HISTOLOGICAL STRUCTURE (Academia Science Repository, 2023)
The kidneys are paired retroperitoneal organs of the urinary system. Their function is to filter blood and produce urine. Each kidney consists of a cortex, medulla and calyces. The nephron is the main functional unit of the kidney, in charge of removing metabolic waste and excess water from the blood. In this article we will explore the microanatomy of a nephron and learn how their function relates to their histological features.